2019
DOI: 10.5327/z2176-947820190472
|View full text |Cite
|
Sign up to set email alerts
|

Derramamento De Petróleo E Seus Impactos No Ambiente E Na Saúde Humana

Abstract: A exploração petrolífera envolve atividades com alto índice poluidor quepodem prejudicar a qualidade da água, do solo, do ar e, consequentemente,a qualidade de vida dos seres vivos. A dependência energética mundialpautada nessa indústria causa grande exposição a desastres ambientais nasáreas exploradas, o que torna urgente a intensificação das pesquisas nessecampo. Esta revisão visou identificar estudos sobre os efeitos deletériospara o ambiente e para a saúde das populações em áreas de desastresassociados a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 64 publications
0
8
0
6
Order By: Relevance
“…A study done with the resident population around the Niger River Delta in Nigeria showed that high levels of emotional stress were found in people affected by the oil spill in the region (Nriagu et al, 2016). The work of manually clearing the affected areas can be quite stressful as it is usually done by locals who previously fished in the same region to sell and feed their families (Euzebio et al, 2019). These individuals are more likely to develop depression and post-traumatic stress disorder, like the workers involved in the cleanup of the Gulf of Mexico disaster (Kwok et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…A study done with the resident population around the Niger River Delta in Nigeria showed that high levels of emotional stress were found in people affected by the oil spill in the region (Nriagu et al, 2016). The work of manually clearing the affected areas can be quite stressful as it is usually done by locals who previously fished in the same region to sell and feed their families (Euzebio et al, 2019). These individuals are more likely to develop depression and post-traumatic stress disorder, like the workers involved in the cleanup of the Gulf of Mexico disaster (Kwok et al, 2017).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the impacts on the environment, it is important to highlight that crude oil contains several toxic chemicals, with carcinogenic, non-carcinogenic and mutagenic effects for humans, and the long-term effects on health, including the development of cancer and degenerative disorders resulting from such exposure, may result in a substantial burden of disease in the exposed population (Euzébio et al, 2019).…”
Section: Csimentioning
confidence: 99%
“…Em ecossistemas terrestres, o óleo pode se acumular nas penas e até mesmo no fígado de aves. Além disso, ocorre prejuízo na ação fotossintética de plantas em manguezais 24 . No acidente da plataforma no Golfo do México as consequências para a diversidade marinha, em âmbito da zona pelágica, foi a mortandade de larvas de peixes, o que pode ter causado a perda de uma geração desses peixes.…”
Section: Efeitos Tóxicos Dos Componentes Do Petróleo No Ecossistemaunclassified
“…A limpeza das áreas afetadas é considerada um fator estressor. Isso porque, em geral, é realizada manualmente pela população local das áreas afetadas, especialmente por indivíduos que utilizam o mar como fonte de sustento ou complemento de renda e alimentação 24 .…”
Section: Aspectos Psicossociais E Psicológicos Associados Ao Derramam...unclassified